Development and characterization of 1, 1-bis(3-methyl-4-hydroxyphenyl) cyclohexane-based benzoxazine and cyanate ester hybrid polymer matrices: Thermal and morphological properties. Issue 9 (November 2019) - Chozhan, C Karikal; Chandramohan, A; Alagar, M
1, 1-Bis(3-methyl-4-hydroxyphenyl)cyclohexane-based benzoxazine monomer and 1, 1-bis(3-methyl-4-cyanatophenyl)cyclohexane were blended together via in situ polymerization. The chemical blending of benzoxazines with cyanate ester was carried out thermally and the resulting product was analyzed by Fourier transform infrared spectra. The benzoxazine–cyanate ester hybrid polymer matrices were investigated for their thermal and morphological properties. The glass transition temperature, curing behavior, thermal stability, char yield, and flame resistance of the hybrid polymer matrices were studied by means of differential scanning calorimeter and thermogravimetric analysis.